Km-scale mounds and sinkites formed by buoyancy driven stratigraphic inversion - Jan Erik Rudjord; Mads Huuse (Communications Earth & Environment)
Abstract Oligo-Miocene strata in the northern North Sea comprise hundreds of enigmatic km-scale sand-cored mounds. We investigated these using a basin-scale 3D seismic dataset coupled with petrophysical logs and cuttings mineralogy for hundreds of wells. Here we document the discovery of ‘sinkites’, large-scale sand bodies that have sunk into and underpin low-density bio-silicious ooze rafts, violating the law of superposition. The stratigraphic inversion is attributed to buoyancy instabilities between km-scale rigid low density ooze rafts and liquefied, younger, denser, unconsolidated sand. The sand slurry dislodged the ooze as rafts, delimited by early-stage polygonal faults formed due to volumetric contraction of underlying ooze packages. Akin to load casts, but orders of magnitude bigger, ‘sinkites’ introduce a new large-scale gravitational process into geology. Their discovery and association to fractured low density ooze is important to stratigraphy and assessments of reservoir, seal and fluid flow in petroleum and CO2 storage projects and may have other implications.